Volver la vista der umgekehrte Blick = The gaze back - Palm, Michael 1965- (Schönwiese, 2005)
"Moves the viewer into the perspective of a foreigner. Mexicans who live in Austria and Austrians who spend their lives in Mexico: through clichés, yearnings, and personal experience, they create a picture of their ideas about the countries where they came from, and through determining their location, attempt to their identity. [...]" [Cover]